Global Dynamics of Corruption: Analyzing Regional Bodies' Role in Building Integrity and Effectiveness in the Fight Against Corruption - Lal Bullu, Saphy (Faculty of Law, Universitas Lampung, 2024)
This article analyzes the global dynamics of selected regional bodies in promoting integrity and effectiveness in the fight against corruption. The widespread recognition of corruption in the early 1990s led to the formation of regional bodies aimed at fostering integrity and developing effective instruments for global corruption eradication. The findings reveal that while each regional body is unique in its history and structure, there are similarities that are often transferable. However, ambiguities in definitions, criminalization of acts, and preventive measures undermine the effectiveness of these systems and limit their potential to reinforce comprehensive integrity in the fight against corruption. This article employs both qualitative and quantitative methods to review existing literature, generate data, and assess the role of regional bodies in building integrity and combating corruption.